2021
DOI: 10.1021/acsomega.1c01588
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of Immersion in Caffeine and Glyphosate Aqueous Solutions of SBA-15 and Amino-Functionalized SBA-15

Abstract: Mesostructured silica SBA-15 and amino-functionalized silica SBA-15-NH 2 were synthesized, and then, characterization, adsorption capacity, and immersion enthalpies in caffeine and glyphosate on SBA-15 and SBA-15-NH 2 were evaluated. The enthalpy parameter was determined using a local construction Tian-type heat conduction calorimeter. Calorimetric studies in caffeine solutions exhibit negative enthalpy values; exothermic process characteristics for SBA-15 were bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…C/S/SBA‐15 is composed of short rods with a size of approximately 1 μm, as shown in Figure 1B. The observed morphology is similar to that previously observed for silica SBA‐15, [26] suggesting that the sulfur‐doped carbon does not aggregate on the outer surface of silica SBA‐15 and that carbon loading occurs on the inner walls of silica. In addition, energy dispersive spectroscopy (EDS) mapping of C, O, S, and Si in the sample demonstrated that these elements were homogeneously dispersed in C/S/SBA‐15.…”
Section: Resultssupporting
confidence: 78%
“…C/S/SBA‐15 is composed of short rods with a size of approximately 1 μm, as shown in Figure 1B. The observed morphology is similar to that previously observed for silica SBA‐15, [26] suggesting that the sulfur‐doped carbon does not aggregate on the outer surface of silica SBA‐15 and that carbon loading occurs on the inner walls of silica. In addition, energy dispersive spectroscopy (EDS) mapping of C, O, S, and Si in the sample demonstrated that these elements were homogeneously dispersed in C/S/SBA‐15.…”
Section: Resultssupporting
confidence: 78%
“…Mesoporous silicon materials possess an ordered pore structure, high specific surface area, and abundant modifiable sites of silicon hydroxyl. 26,27 In recent years, metal-doped SBA-15 porous materials have been widely applied as ideal adsorbents in the removal of different pollutants, such as metal ions in wastewater, sulfur and nitrogen compounds in oil, small organic molecules and CO 2 . [28][29][30][31] It has advantages such as stability, good dispersibility in water, and good recovery performance.…”
Section: Introductionmentioning
confidence: 99%
“…SBA-15 has unique excellent properties, such as large pore size, large specific surface area, high orderliness, and high hydrothermal stability. , Moreover, the surface of the SBA-15 material is rich in Si–OH groups, which can load a large number of organic and inorganic functional groups by condensation or grafting, leading it to be one of the promising adsorbent or catalytic materials. , Sousa et al used a post-synthesis method to load ZnO onto SBA-15 for the adsorption of ciprofloxacin, and the adsorption capacity of the ZnO-SBA-15 was proportional to the incorporated amount of ZnO while maintaining the mesoporous structure of SBA-15. Rodríguez-Estupiñan et al synthesized amino-functionalized SBA-15 by a post-grafting method and compared it with SBA-15 for the adsorption of caffeine and glyphosate in aqueous solution. The results showed that the amino-functionalized SBA-15 material produced a difference in the physical and chemical properties of the solids.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 SBA-15 has unique excellent properties, such as large pore size, large specific surface area, high orderliness, and high hydrothermal stability. 13,14 Moreover, the surface of the SBA-15 material is rich in Si−OH groups, 15 which can load a large number of organic and inorganic functional groups by condensation or grafting, leading it to be one of the promising adsorbent or catalytic materials. 16,17 Sousa et al 18 of ciprofloxacin, and the adsorption capacity of the ZnO-SBA-15 was proportional to the incorporated amount of ZnO while maintaining the mesoporous structure of SBA-15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation